TEKS TUTUR ANGKUS PRANA: KAJIAN STRUKTUR DAN SEMIOTIKA - Dewi Santhiastini, Ni Kadek; Suardiana, I Wayan; Nala Antara, I Gde (Humanis; Volume 16. No. 2. Agustus 2016, 2016)
This research on Tutur Angkus Prana is to discuss on structural study and semiotic matters. The aim of this structural analysis is to assess the manuscript structure, and so the semiotic analysis is to analyze signs on Tutur Angkus Prana that contain a specific meaning. The result of this research is the unfolding and explanation on Tutur Angkus Prana that is involved with intrinsic structure on the relevant text, that is usada, mantra, upakara, and language style. The understanding of Bapa and Ibu on Tutur Angkus Prana, karma and reincarnation, and kamoksan (kalepasan) as symbols.